Continued Elevation of Plasma IL-4 and IL-17 Predicts the Progression from VMC to DCM. (11th January 2020) - Wang, Z. H.; Liao, Y. H.; Yuan, J.; Jin, X. J.; Yu, M.; Chen, R. Z.; Xu, D. J.; Wei, J.; Wan, J.; Zhao, D. C.; Han, H. Y.; Li, B.; et al.
Abstract : Objective . To investigate plasma cytokines (interferon gamma, interleukin-4, and interleukin-17) in patients with viral myocarditis (VMC) and evaluate their predictive value in the progression from VMC to dilated cardiomyopathy (DCM). Methods . A prospective, multicenter, observational study included 536 patients with newly diagnosed VMC admitted in cardiology departments of 24 tertiary super specialised university-affiliated hospitals in the China registry from January 2012 to June 2016. Demographics and clinical characteristics at baseline and after three months were collected, including laboratory blood tests, ECG, echocardiography, and drug treatment in each participating site. The plasma anti-viral antibodies (Abs), anti-heart autoimmune Abs, and cytokines were detected by ELISA. Results . Of the 536 patients, 534 were included for analysis after two patients died in less than a month. The plasma levels of IFN- γ, IL-4, and IL-17 were continually higher in patients with incident DCM than in those without incident DCM at baseline, from the 1st month and the 3rd month; all had a P value of <0.0001. There was a positive correlation between IL-4 and LVEDd (r = 0.30, P < 0.0001 ) and between IL-17 and LVEDd (r = 0.11, P = 0.02 ). When all these covariates have entered the model simultaneously, elevated IL-4 and IL-17 were still significantly associated with DCM incidence. The RR (95% CI) of DCM incidence were 1.04 (1.02-1.06) for IL-4 and 5.24 (2.81-9.79) for IL-17. Conclusion . The continued elevation of plasma IL-4 and IL-17 in VMC patients were associated with a high incidence of DCM at three months, and these two cytokines were independent predictors for the progression from VMC to DCM.